2017
DOI: 10.1175/wcas-d-16-0029.1
|View full text |Cite
|
Sign up to set email alerts
|

Are Smallholder Farmers’ Perceptions of Climate Variability and Change Supported by Climate Records? A Case Study of Lower Gweru in Semiarid Central Zimbabwe

Abstract: The livelihoods of the majority of people in semiarid areas of developing nations are based on rain-fed agriculture. In the wake of climate variability and change, communities in these regions are the most vulnerable because of their limited capacities to adapt to environmental changes. Smallholder farmers in the study area, Lower Gweru in central Zimbabwe, ascertain that they have observed changes in some rainfall and temperature patterns. These changes include higher temperatures, an increased number of seas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 21 publications
2
14
0
Order By: Relevance
“…Such a drying trend is consistent with previous ndings for other parts of southern Africa e.g. (Daron 2014;Morioka et al 2015;Scholes et al 2015) and Zimbabwe in general (Brazier 2015;Makuvaro et al 2017;Nangombe et al 2018). However, while there is generally decreasing total annual precipitation (mean = -0.54mm/annum), this is accompanied by increased precipitation intensity (marked by increasing maximum 1-day precipitation amounts (RX1Day)) over most of the study region.…”
Section: Discussionsupporting
confidence: 92%
“…Such a drying trend is consistent with previous ndings for other parts of southern Africa e.g. (Daron 2014;Morioka et al 2015;Scholes et al 2015) and Zimbabwe in general (Brazier 2015;Makuvaro et al 2017;Nangombe et al 2018). However, while there is generally decreasing total annual precipitation (mean = -0.54mm/annum), this is accompanied by increased precipitation intensity (marked by increasing maximum 1-day precipitation amounts (RX1Day)) over most of the study region.…”
Section: Discussionsupporting
confidence: 92%
“…perception. This result is in agreement with studies conducted in Ghana (Amadou et al, 2015, Asare-Nuamah), Niger (Assoumana et al, 2016), Nigeria (Ayanlade et al, 2017) and central Zimbabwe (Makuvaro et al, (2018). On the contrary Ouedraogo et al, (2010); Ulrich et al, (2015); Bambara, et al, (2016) reported that farmers perceive changes in climatic variables such as a decrease in rainfall, an increase in temperature, the late or early start of the season and the short duration of the season, etc., which was in contradiction with our results.…”
Section: Temperature Onset Of Rainy Seasonsupporting
confidence: 93%
“…Therefore, farmers in Benguene may not be a reliable source of long-term changes in rainfall, but they could provide reliable information on inter-and intra-seasonal rainfall changes. Authors such as Makuvaro et al, (2018) suggest studies on comparisons of perceptions and trends based on smaller time scales rather than long periods. This is particularly important when such studies seek communities' responses.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of climate variability on crop production of a region has been studied by observing local perceptions in different regions of the globe [30,31]. In the present study, we also visited different sites for verification of change on the ground and recorded narratives of local farmers on the changes.…”
Section: Field Surveymentioning
confidence: 99%